Storage stability of kernels and oil of normal and oleic acid rich groundnut Varieties: Storage stability of kernels and oil of normal and oleic acid rich groundnut Varieties - K C DILEEPA; S HEMALATHA (Journal of Oilseeds Research, 2020)
The oleic acid rich groundnut variety (Dh 245) and normal groundnut variety (GPBD 4) were kept for storage in the form of kernels as well as oil for six months to study the storage stability. Peroxide value and free fatty acids increased at lower rate in Dh 245 compared to GPBD 4 variety in both kernels and oil. In case of fatty acid composition, the per cent decrease in the linoleic acid content and U/S ratio was lower in Dh 245 variety compared to GPBD 4 variety in both kernels and oil. This indicated that Dh 245 variety has good storage stability than GPBD 4 variety. Oxidation rate of kernels was lower than oil during storage.